2019
DOI: 10.3390/catal9060497
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Based Catalysts Supported on Two Kinds of Beta Zeolite for Application in Fischer-Tropsch Synthesis

Abstract: Co-containing Beta zeolite catalysts prepared by a wet impregnation and two-step postsynthesis method were investigated. The activity of the catalysts was examined in Fischer-Tropsch synthesis (FTS), performed at 30 atm and 260 °C. The physicochemical properties of all systems were investigated by means of X-ray diffraction (XRD), in situ XRD, temperature programmed desorption of ammonia (NH3-TPD), X-ray Photoelectron Spectroscopy (XPS), temperature programmed reduction of hydrogen (TPR-H2), and transmission e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 50 publications
(50 reference statements)
2
11
0
Order By: Relevance
“…Both Red-Mi-co-Ni3.0Co10AlBeta and Red-Me-co-Ni3.0Co10AlBeta exhibit a lower CO conversion (17%), but a higher liquid hydrocarbon selectivity (96%-99%). It is worth mentioning that all samples, except Red-Me-Ni3.0Co10SiBeta, exhibit higher CO conversion than Co-based systems [25,64]. A similar conclusion was reported by Wang et al for Ru, Ni promoted Co/HZSM-5 catalysts [2].…”
Section: Fischer-tropsch Synthesissupporting
confidence: 84%
See 1 more Smart Citation
“…Both Red-Mi-co-Ni3.0Co10AlBeta and Red-Me-co-Ni3.0Co10AlBeta exhibit a lower CO conversion (17%), but a higher liquid hydrocarbon selectivity (96%-99%). It is worth mentioning that all samples, except Red-Me-Ni3.0Co10SiBeta, exhibit higher CO conversion than Co-based systems [25,64]. A similar conclusion was reported by Wang et al for Ru, Ni promoted Co/HZSM-5 catalysts [2].…”
Section: Fischer-tropsch Synthesissupporting
confidence: 84%
“…The microporous catalysts exhibit a higher chain growth probability value than mesoporous ones. A similar dependency was observed for Co zeolite catalysts in our earlier works [25,64]. The chain growth probability for the gaseous product of the FTS (α for C 1 -C 4 selectivity) for all samples, except Red-Ni 3.0 Co 10 AlBeta and Red-Ni 3.0 Co 10 SiBeta, shows the opposite tendency than α for C 5+ selectivity.…”
Section: Fischer-tropsch Synthesissupporting
confidence: 83%
“…Based on the results, the diffraction peaks of Co metal oxides were recorded at 2 = 42.40°, 36.50°, dan 61.52°. However, Sadek et al (2019) reported that the oxide phase of Co metal was observed at 2 = 36.80°, 59.30°, dan 65.20° [24]. On the other hand, the diffraction peaks for Mo metal were reported at 2θ = 57.76° and 72.87° [25].…”
Section: Catalysts Characteristicsmentioning
confidence: 98%
“…Several cobalt compounds are oxidation catalysts. However, over the past decade cobalt-based catalysts were widely utilized in reactions involving CO, such as in the hydrogenation of CO into liquid fuels in Fischer-Tropsch process [87][88][89]. A study conducted by van Deelen et al indicates that supported cobalt particles of less than 6 nm are less stable in Fischer-Tropsch processes.…”
Section: Cobalt Nanoparticles As Catalystsmentioning
confidence: 99%